2020
DOI: 10.33490/jkm.v6i2.234
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Ibu Hamil Berhubungan dengan Pengetahuan dalam Penggunaan Kontrasepsi Pasca Persalinan

Abstract: Pregnancy is a maturation crisis that can be stressful. The maturation crisis can be overcome if the mother is ready to enter a new phase where she is ready to take on the responsibilities of being a parent and a new role so that the mother must take care of her health to prevent complications of pregnancy. Pregnancy complications can be prevented by maintaining the distance of pregnancy between one child with another child through postpartum contraception. The study aimed to determine the characteristics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
1
0
2
Order By: Relevance
“…This study is in line with the results of the study (Sari et al, 2020) that the results of the bivariate analysis showed that education had a significant relationship with maternal knowledge in the use of postpartum contraception with p value = 0.002. This happens because the majority of mothers' education is high school so that mothers are able to use search for information independently using online media, so that the information obtained can increase mother's knowledge, besides that pregnant women are also diligent in visiting health services around their homes.…”
Section: An Overview Of the Level Of Knowledge Of Pregnant Women In T...supporting
confidence: 91%
See 1 more Smart Citation
“…This study is in line with the results of the study (Sari et al, 2020) that the results of the bivariate analysis showed that education had a significant relationship with maternal knowledge in the use of postpartum contraception with p value = 0.002. This happens because the majority of mothers' education is high school so that mothers are able to use search for information independently using online media, so that the information obtained can increase mother's knowledge, besides that pregnant women are also diligent in visiting health services around their homes.…”
Section: An Overview Of the Level Of Knowledge Of Pregnant Women In T...supporting
confidence: 91%
“…Based on the number of children, mothers who have a good attitude are mothers who have <3 children as many as 6 people (33.3%) and those who have less attitudes are mothers who do not have children as many as 4 people (44.4%). This is the same as the study (Sari et al, 2020) that the results of the bivariate test showed the number of children had a significant relationship with mother's knowledge of postnatal contraceptive use with p value = 0.006).…”
Section: Overview Of the Third Trimester Pregnant Women's Attitudes A...supporting
confidence: 82%
“…Research conducted by Naluri and Prasetyo [30] stated that women with higher education tend to get jobs and increased incomes; therefore, these women do not have problems with children because they can support their families. Individuals with higher education have broader knowledge, but that does not mean individuals with lower education must also have less understanding because increased knowledge does not only come from formal education but also from non-formal education [31].…”
Section: Discussionmentioning
confidence: 99%
“…Oleh karena itu, penggunaan alat kontrasepsi memerlukan perhatian khusus karena dapat menyebabkan gangguan fungsi seksual. 31 Menurut asumsi peneliti, Setiap jenis KB memiliki kelebihan, kelemahan dan efek sampingnya masing-masing namun pada kebanyakan kasus penurunan gairah seksual merupakan efek samping yang dapat dijumpai pada setiap penggunaan jenis KB meskipun penurunan gairah seksual dapat terbentuk tidak hanya dari penggunaan KB, namun juga ada banyak faktor lain yang dapat memberikan pengaruh terhadap perilaku dan juga keinginan yang nantinya akan memicu terjadinya penurunan gairah seksual. Hal ini dikarenakan KB Suntik DMPA mengandung progesterone yang efek kerjanya adalah antietrogenik, sehingga penggunaan jangka panjang dapat mengakibatkan defisiensi estrogen sebagian.…”
Section: Pembahasanunclassified